Historically unprecedented global glacier changes in the 1 early 21st century - Zemp, Michael; Frey, Holger; Gärtner-Roer, Isabelle; Nussbaumer, Samuel U.; Hoelzle, Martin; Paul, Frank; Haeberli, Wilfried; Denzinger, Florian; Ahlstrøm, Andreas P.; Anderson, Brian; Bajracharya, Samjwal; Baroni, Carlo; et al. (Journal of Glaciology)
Observations show that glaciers around the world are in retreat and losing mass. Internationally coordinated for over a century, glacier monitoring activities provide an unprecedented dataset of glacier observations from ground, air and space. Glacier studies generally select specific parts of these datasets to obtain optimal assessments of the mass-balance data relating to the impact that glaciers exercise on global sea-level fluctuations or on regional runoff. In this study we provide an overview and analysis of the main observational datasets compiled by the World Glacier Monitoring Service (WGMS). The dataset on glacier front variations (∼42 000 since 1600) delivers clear evidence that centennial glacier retreat is a global phenomenon. Intermittent readvance periods at regional and decadal scale are normally restricted to a subsample of glaciers and have not come close to achieving the maximum positions of the Little Ice Age (or Holocene). Glaciological and geodetic observations (∼5200 since 1850) show that the rates of early 21st-century mass loss are without precedent on a global scale, at least for the time period observed and probably also for recorded history, as indicated also in reconstructions from written and illustrated documents. This strong imbalance implies that glaciers in many regions will very likely suffer further ice loss, even if climate remains stable. Fil: Zemp, Michael. Universitat Zurich; Suiza Fil: Frey, Holger. Universitat Zurich; Suiza Fil: Gärtner-Roer, Isabelle. Universitat Zurich; Suiza Fil: Nussbaumer, Samuel U. Universitat Zurich; Suiza Fil: Hoelzle, Martin. Universite de Fribourg; Suiza. Universitat Zurich; Suiza Fil: Paul, Frank. Universitat Zurich; Suiza Fil: Haeberli, Wilfried. Universitat Zurich; Suiza Fil: Denzinger, Florian. Universitat Zurich; Suiza Fil: Ahlstrøm, Andreas P. Geological Survey Of Denmark And Greenland; Dinamarca Fil: Anderson, Brian. Victoria University Of Wellington; Nueva Zelanda Fil: Bajracharya, Samjwal. International Centre For ...